Prevalence and Antifungal Susceptibility of Candida Species Isolated from Women Attending a Gynaecological Clinic in Kumasi, Ghana (Journal of Science and Technology, 2016)
Candidal vulvovaginitis causes extreme discomfort and affects the well being of women. The aim of this study was to determine the prevalence of Candida infections among women attending gynaecological clinic at the Komfo Anokye Teaching Hospital (KATH) in Kumasi and the antifungal susceptibility patterns of the Candida species isolated. A total of 186 high vaginal swabs (HVS) were collected from women suspected of having candidal vulvovaginitis between March and June 2009. Wet mount preparations in potassium hydroxide (KOH) and Gram-stained smears were performed directly on specimens. Cultures for Candida species were done using sabouraud dextrose agar (SDA) (Oxoid, UK) at room temperature (25 - 28ºC). Antifungal susceptibility of the Candida species to amphotericin B, fluconazole and itraconazole was assessed using the ATB FUNGUS 3 test kits (bioMerieux, Marcy-l’Etoile, France). Of the 186 HVS cultured, 39 yielded Candida species giving Candida prevalence in HVS during the study period as 21%. Candida species isolated from HVS specimens were Candida albicans (n=19, 48.7%), Candida glabrata (n=7, 17.9%), Candida tropicalis (n=4, 10.3%) and Candida dubliniensis (n=4, 10.3%). Other species isolated were Candida sake (n=2, 5.1%), Candida krusei (n=2, 5.1%) and Candida parapsilosis (n=1, 2.6%). Susceptibility of the isolates to antifungal agents ranged from 66.7% to 87.2% with MICs ranging from ≤ 0.125mg/l to 8mg/l. Amphotericin B was the best performing antifungal agents with sensitivity of 87.2%.